Infectious and noninfectious epiglottitis in adults: our experience - Altaf Malik; Muzaffar, Rahil; Sumat Ul Khurshid (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The present prospective study was conducted in the department of ENT at GMC Doda for a period of three years from February 2019 to March 2022. The study aimed at evaluating the causes, presentation and management of adult epiglottitis. Methods: The patients presenting with the sign and symptoms of epiglottitis were evaluated and were subjected to rigid/flexible endoscopic examination. Patients presenting with respiratory distress were categorized as per Freidman’s classification. Results: Epiglottitis was seen in 21 patients with 13 male and 8 female patients. The age distribution was between 26 and 68 years (mean, 44.4±11.3). Infection, as a cause of epiglottitis was present in 14 subjects and 7 patients had non infectiousetiology. Corrosive ingestion (HCL) and angioedema was seen in two patients each. Hot water aspiration, hot milk and foreign body aspiration (fish bone) was present in the rest of three patients each. Most common complaint of patients in our study was sore throat followed by painful swallowing and voice change. Conclusions: Epiglottitis in adults can be easily overlooked because of its non-specific presentation. Importance needs to be stressed upon the examination of larynx in patients presenting with sore throat not responding to conventional treatment or with symptoms of respiratory distress and voice change. Airway management should be take preference in patients having stridor before embarking on laryngeal examination with close Follow up.